ANALISIS YURIDIS DINAMIKA TINDAK PIDANA DALAM PERSPEKTIF PERTANGGUNGJAWABAN KORPORASI - Jeane N. Saly (to-ra, 2015)
AbstractThe impact of globalization has not only resulted in growth of increasingly thin state border, butalso growth of legal events that are not only private, but also be public, as a criminal offense, whichrequires accountability as a result of the activities of large companies (corporate) in their activities,to the detriment public (public). The problem is how the development of corporate criminal offensesettings and is responsible under the law in Indonesia, and other countries. The conclusion is thatthe offense and the responsibility of corporations in Indonesia are not regulated in the CriminalJustice Act (Criminal Code), but scattered in various legislation. The next development, both incriminal law and administrative law that have criminal sanctions have largely been set up ofcorporate as subjects of criminal law. In fact, in the General Explanation of the first bookmanuscript draft Law Code of Criminal Law (Draft-Criminal Code) 1999-2000 recognized. Inother countries, criminal offense of corporate and its accountability is set up, especially thecountries adherents of the common law system, are like the UK, the USA, and Canada, whichstarted in the industrial revolution 1842. The district court in its decision to apply through penaltiesfor the corporate fails to perform obligations under the legislation.Kata Kunci: Dinamika Tindak Pidana dan Pertanggungjawaban korporasi